Impact of body mass index and examination type on utilization of screening programs: A big data study - Udi, Yarin; Gilad-Bachrach, Ran; Cohen, Hilla; Sagi-Dain, Lena (Preventive medicine, 2024)
To investigate the relationship between Body Mass Index (BMI) and adherence to recommended screening tests, addressing gaps in previous literature by utilizing a large cohort, while considering longitudinal changes in weight and the type of screening. Data from Clalit Health Services in Israel were retrospectively analyzed, including participants aged 50 and above from 2002 to 2021. BMI measurements and various screening test records were examined. Generalized Estimating Equations were employed for analysis, adjusting for potential confounding variables, including age, gender, geographic location, and socioeconomic status. The study included 634,879 participants with 4,630,030 BMI measurements and 56,453,659 test records. Participants were categorized into BMI cohorts at the time of the test, with overweight and obese individuals showing lower odds of undergoing intimate examination-based screening tests (mammography, PAPS, and skin examination), as opposed to higher odds of several non-intimate tests (e.g., diabetes and eye disorder screenings). Our findings suggest that individuals with overweight and obesity are less likely to undergo screenings involving intimate physical examinations, potentially due to weight stigma and discomfort. This avoidance behavior may contribute to increased morbidity rates in these populations. Interventions addressing weight stigma, improving access to care, and enhancing patient engagement are warranted.